Lockdown to Contain the COVID-19 Pandemic: An Opportunity to Create a Less Polluted Environment in India - Preet Lal; Amit Kumar; Supriya Bharti; Purabi Saikia; Dibyendu Adhikari; M. L. Khan (Aerosol and Air Quality Research)
Abstract Keeping aside the economic consequences, the imposition of strict lockdown in order to break the chain of deadly infection of SARS-CoV-2, has potentially improved the global environmental quality by facilitating a significant reduction in atmospheric pollution. In the present study, the level of atmospheric pollutants in India viz., NO2, AOD, and PM2.5 before and during lockdown 2020 were assessed and compared using standard methods. The study revealed a significant reduction in NO2 i.e., > 10% change in 73.71% parts in India along with a high negative anomaly of AOD (< –1.0 in 32.92% parts in India) primarily in the Indo-Gangetic Plains, western, southern, and eastern parts during the lockdown. The five megacities observed a sharp decline in the daily mean concentration of PM2.5 (ca. 32% (Delhi) to 59.62% (Bengaluru) during the lockdown 2020 as compared to the analogous period of lockdown in 2019. The study exhibited the very less contribution of seasonal and meteorological variables in the abatement of pollution during the lockdown period. The findings may be useful in guiding future strategies to maintain environmental quality by adopting a well-planned lockdown strategy.